The importance of antibiotics and the evolution of resistance to antimicrobial substances - Adrian Rădulescu; Maria Crivineanu; Diana Mihaela Alexandru (Medicamentul Veterinar, 2024)
By exploring the history of antibiotic discovery and how antimicrobial resistance has become a global problem, this study aims to provide a comprehensive perspective on the impact of these factors on public health. At the same time, we will analyze the strategies proposed to counter this worrying development and to ensure a future in which antibiotics remain effective tools in the treatment of bacterial infections. The purpose of this paper is to review proposed strategies for countering antimicrobial resistance, including the development of new antibiotics, improved prescribing practices, and public awareness of the responsible use of these drugs. In an era where treatment-resistant infections are becoming more common, it is crucial that we engage in concerted efforts to maintain the effectiveness of antibiotics and ensure the future health of the global population.